Expert System for Predicting Cadmium Pollution - Vengidason, Yogavaeni (1998)
Expert System for predicting cadmium (Cd) pollution was developed using Visual Basic incorporated with CLIPS. The information was obtained from a primary data to develop this expert system. Sediment was used as an indicator of Cd pollution because of it's permanency compared to water itself and reported to be the sink for trace metals. The data obtained showed that in the dry season there was a significant change in the concentration of Cd. The Cd concentration increased from before the source to after the source of pollution. In the wet or semi-wet seasons, the overall Cd concentration reduced because the washout effect caused by the increase in the quantity of river water. As a result, the concentration of Cd before, at and after the source of pollution became about the same for the wet and the semi-wet seasons. This two points were used as a guide to come up with a theory to structure and develop the expert system. The user of the expert system is required to key in the before and after the source of pollution data and the Cd concentration in the water data, so that the system could process these data and predict the present and future level of heavy metal (Cd) pollution. The prediction and information provided in the system enabled user to produce a good EIA report on Cd pollution in the aquatic environment.